Effects of alloying element on weld characterization of laser-arc hybrid welding of pure copper. (June 2018) - Hao, Kangda; Gong, Mengcheng; Xie, Yong; Gao, Ming; Zeng, Xiaoyan
Highlights: Elements Si and Sn benefits the growth of column grains within fusion zone (FZ). The microhardness and strength of FZ are increased by solution strengthening. The conductivities of the welds are decreased by alloying elements. The weld corrosion resistance increases due to the compact Cu/Si oxidation film. Abstract: Effects of alloying elements of Si and Sn on weld characterizations of laser-arc hybrid welded pure copper (Cu) with thickness of 2 mm was studied in detail by using different wires. The weld microstructure was analyzed, and the mechanical properties (micro-hardness and tensile property), conductivity and corrosion resistance were tested. The results showed that the alloying elements benefit the growth of column grains within weld fusion zone (FZ), increase the ultimate tensile strength (UTS) of the FZ and weld corrosion resistance, and decrease weld conductivity. The mechanisms were discussed according to the results.